Discrepancy of Home-Based School Regulation in West Jakarta Study Case of Student High School of 78 and 16 - Nisa Maulia; Raldi H Koestoer; Ratna Saraswati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
The Local Government has been limiting prospective students by implementing home-based school regulations since 2013. The study highlights the spatial pattern of trip distribution of Student High School of 78 and 16 in which both are located near the west border of Jakarta as the impact of government regulation. Primary data were collected using questionnaires and GPS receiver used to capture the coordinate points of schools and students’ home address. Secondary data included Administrative and Road Network Map. The methods applied involved Mapping Network Analysis and Statistical Cross Tabulation. Network analysis was performed to evaluate nearest school to student and a set of origin-destination (OD) matrix. Cross tabulation was applied to evaluate the frequency of student travel pattern. The analyses showed that Student High School of 78 trip distribution was widen and widespread than of Student High School 16.